DETERMINATION MODEL OF ORIGIN-DESTINATION MATRIX NATIONAL RICE COMMODITY BY USING SEA MODE - ANGELIA 23409025); Pembimbing : Suprayogi, Ph.D, CORRY
Rice is the primary commodity in Indonesia society. Increasing number of population every year, makes the need of rice must be considered by each province. Rice distribution will be moved from surplus areas (production centre) to minus areas. So, the origin-destination matrix is used to determine rice distribution from every province of origin to any destination province. The purpose of this research is to determine origin-destination matrix national rice commodity for year 2009. It took a few steps to reach the origin-destination matrix for 2009. Stages begin with determination of model origin-destination matrix national rice for year 2009 by using simultaneous model approach. This process produce the quantity of rice shipped from each province of origin to destination province. Matrix balancing is used to ensure the quantity of production and attraction rice become balance by using transportation gravity model. Thus, the quantity of production and attraction rice can be known. The result of this research produce equation model that can be used to estimate origin-destination matrix of national rice commodity for year 2009. The quantity of production and attraction produced 4.780.966 tons and 4.639.365 tons. After balancing, the quantity of production and attraction rice commodity has the same value is 4.780.966 tons.